2005
DOI: 10.2106/jbjs.d.01773
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Slipped Capital Femoral Epiphysis in Amish Children

Abstract: Although the children in this study were moderately heavy, they could not be classified as obese on the basis of weight-for-age or body-mass-index percentiles. The high prevalence of family members with slipped capital femoral epiphysis may reflect either a genetic or environmental component, or an interaction between genetics and environment (for example, work load or common chores requiring particular physical positions) in the Amish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…1 In certain communities, there appears to be a particularly higher incidence of familial slipped capital femoral epiphysis. 1,2 There is also increasing interest in the possible association of this disease with various human leukocyte antigen types. [3][4][5][6] We report a pair of brothers who presented with slipped capital femoral epiphysis within a year.…”
Section: Slipped Capital Femoral Epiphysis In Two Indian Brothers -Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 In certain communities, there appears to be a particularly higher incidence of familial slipped capital femoral epiphysis. 1,2 There is also increasing interest in the possible association of this disease with various human leukocyte antigen types. [3][4][5][6] We report a pair of brothers who presented with slipped capital femoral epiphysis within a year.…”
Section: Slipped Capital Femoral Epiphysis In Two Indian Brothers -Th...mentioning
confidence: 99%
“…These studies were done in stable populations where there may be inbreeding. 2 In his family studies, Rennie 1 suggested that autosomal dominant inheritance with variable penetrance was the likely mode of inheritance. However, he also noted a possibility of an autosomal recessive mode of inheritance in a smaller proportion of patients.…”
Section: Slipped Capital Femoral Epiphysis In Two Indian Brothers -Th...mentioning
confidence: 99%